EFFECTS OF PARTICLE SIZE, EXTRACTION TIME, AND SOLVENT ON DAIDZEIN YIELD EXTRACTED FROM TEMPEH - Sri Hartati Yuliani; Petrus Damiani Tosan Aji; Arini Safti Sandrapitaloka; Fransiska Revana Restiana; Michael Raharja Gani; Florentinus Dika Octa Riswanto (Sanata Dharma University, 2019)
Daidzein, one of the isoflavone aglycones contained in tempeh, has several biological activities such as anti-inflammatory, anti-oxidant, anti-breast cancer, and suppression of expression of matrix metalloprotease-9. As a fermented product from soybeans, daidzein content in tempeh was found in higher concentration compared to the soybean raw material. It was important to optimize several factors affecting extraction process such as particle size of tempeh simplicia, extraction time, and solvent in order to develop an effective method for the daidzein isolation from the tempeh or other natural products. Evaluation of extraction factors was conducted by applying variations for each factor followed by quantitative analysis using HPLC methods. The optimization condition was performed by daidzein standard and achieved with the particle size of tempeh simplicia of 1.2 mm, extraction time of 360 minutes, and 70% ethanol was used as solvent. Furthermore, the optimized condition was applied for the daidzein isolation from tempeh, a soybean fermented product.